Optical and Structural Properties of Quantum Dots - Yukselici, M. H.; Bozkurt, A. Asikoglu; Allahverdi, C.; Nassar, Z.; Bulut, D.; Omur, B. Can; Torun, M. K.; Ince, A. T. (SPRINGER INTERNATIONAL PUBLISHING AG, 2016)
We report (i) thickness dependent evolution of structural disorder, strain on crystalline planes and grain size in chemical bath deposited (CBD) CdS thin films studied through a combinative evaluation of the results of optical absorption, Raman spectroscopies, X-Ray diffraction (XRD) and Scanning Electron Microscopy (SEM). (ii) refer briefly to CdSexS1-x nanocrystals in liquid and (iii) address quantum size effect in CdSexS1-x quantum dots embedded in glass studied through steady state photoluminescence spectroscopy. The asymptotic optical absorption edge is red shifted while the long wavelength tail narrows with increasing thickness which is proportional to deposition time. We employ effective mass theory under quantum size effect to estimate average grain size from the energetic position of asymptotic optical absorption edge. The long wavelength tail optical absorption is due presumably to the micro-electric field induced by crystalline defects. The transmission probability through the potential energy barrier created by micro-electric field is calculated with the help of WKB (Wentzel, Kramers, Brillouin) approximation. We conclude that as the deposition time increases from 10 to 150 min, the average grain radius changes by 2 nm, Urbach energy and the electric micro-field decrease from 600 to 400 meV and 2240-820 kV/mm respectively. The shift in XRD pattern shows that the compressive strain decreases with growth. The Raman LO1 vibrational mode display an increase up to 22 min of deposition time and then a decrease.
Keywords: CHEMICAL BATH DEPOSITION; CDS THIN-FILMS; RAMAN-SCATTERING; GLASS MATRIX; SOLAR-CELL; PHOTOLUMINESCENCE; NANOCRYSTALS; GROWTH; NANOPARTICLES; CRYSTALLITES; Science & Technology - Other Topics; Optics